Between Good Intentions and Enthusiastic Professors: The Missing Middle of University Social Innovation Structures in the Quadruple Helix - Benneworth, Paul; Cunha, Jorge; Cinar, Ridvan (Regional Helix Ecosystems and Sustainable Growth: The Interaction of Innovation, Entrepreneurship and Technology Transfer, 2020)
This chapter considers the role of universities in stimulating social innovation, and in particular the issue that despite possessing substantive knowledge that might be useful for stimulating social innovation, universities to date have not been widely engaged in social innovation activities in the context of Quadruple Helix developmental models. We explain this in terms of the institutional logics of engaged universities, in which entrepreneurial logics have emerged in recent decades, that frame the desirable forms of university-society engagement in terms of the economic benefits they bring. We ask whether institutional logics could explain this resistance of universities to social innovation. Drawing on two case studies of universities sincerely committed to supporting social innovation, we chart the effects of institutional logics on university-supported social innovation. We observe that there is a “missing middle” between enthusiastic managers and engaged professors, in which four factors serve to undermine social innovation activities becoming strategically important to HEIs. We conclude by noting that this missing middle also serves to segment the operation of Quadruple Helix relationships, thereby undermining university contributions to societal development more generally.
Keywords: Innovation sociale; Quadruple helix approach; Réservé UdeM; Rôle des universités; Université

A dual-functional social innovation process model for low-cost houses through university-enabled initiative - Belayutham, Sheila; Ibrahim, Che Khairil Izam Che; Zulkifli, Assrul Reedza; Ibrahim, Norhati (Construction Innovation-England, 2019)
The purpose of this study is to develop a dual-functional university-enabled social innovation process model on the subject of low-cost houses that addresses the distinct elements of social obligation and university teaching-learning. Design/methodology/approach This study has predominantly adopted a longitudinal single case study approach, where data have been collected through interviews, survey, participant observation, direct observation and document review. The case study details on the social innovation processes, which was conducted by Universiti Teknologi MARA, Malaysia. Findings This study has demonstrated the social innovation processes toward addressing the issue of insufficient low-cost houses, concurrently benefitting the teaching-learning dimension. Three sub-innovations have been highlighted in the developed social innovation process model, which are collaboration process, teaching-learning and design-construct innovation. Originality/value The development of the social innovation process model for low-cost houses through university-enabled initiative is a novel establishment, particularly for developing nations, as limited studies have been conducted in this regard. The significant insights into how university could play a role in addressing major social issues, along with their core focus (teaching-learning and research development), is a breakthrough for further diffusions of social innovation by universities.
Number: 2 N'AVONS PAS ACCÈS
Keywords: Asie; Enseignement; Innovation sociale; Recherche; Rôle des universités; logement

Academic Entrepreneurship for Social Innovation in Taiwan: The Cases of the OurCityLove Platform and the Forest App - Chan-Yuan, Wong; Ying-Che, Hsieh; Ching-Yan, Wu; Mei-Chih, Hu (Science, Technology & Society, 2019)
This study attempts to extend the definition of social innovation within the context of academic entrepreneurship. We consider how academic entrepreneurs can undertake commercial activities, and which ones, and how these activities contribute to the contexts of social innovation. We explore two cases that are derived from two premier universities in Taiwan in terms of research and academic entrepreneurship: OurCityLove from National Chiao Tung University (NCTU) and the Forest app from National Tsing Hua University (NTHU). The two cases show how social enterprises achieved the financial ability to expand their businesses and create the desired social values. While the first case, derived from NCTU, focused on providing useful information on social spaces, and services for the elderly, parents traveling with babies and those with disabilities (and also creating job opportunities for the latter), the other from NTHU created an app to influence those addicted to playing with their smartphones. The cases illustrate how the two universities capitalised on their technological competencies and academic programmes to support graduates and researchers in venturing into social entrepreneurship.
Number: 3 Num Pages: 446-464 Place: Thousand Oaks, United States Publisher: SAGE PUBLICATIONS, INC.
Keywords: Asie; Réservé UdeM; Rôle des universités

A Hub-based University Innovation Model - Prieto Mejia, Samuel; Montes Hincapie, Juan Manuel; Taborda Giraldo, John Alexander; Prieto Mejia, Samuel; Montes Hincapie, Juan Manuel; Taborda Giraldo, John Alexander (Journal of technology management & innovation, 2019)
This article uses a conceptual approach to propose an innovation model for regional universities. It demonstrates that the traditional university encounters several obstacles that hinder its full integration into the development of its respective region and explains why currently known models cannot adapt to regions that have deficient relationships with the government and lack an entrepreneurial base. The new model is based on a structure composed of units called “innovation hubs” and incorporates social innovation, thus permitting the university to become integrated into the regional innovation ecosystems. The Magdalena University in Colombia was used as a reference in developing the model. Keywords: hub; social innovation; university innovation models; regional innovation ecosystems
Number: 1 Publisher: Universidad Alberto Hurtado. Facultad de Economía y Negocios
Keywords: Amérique latine; Colombie; Innovation sociale; Libre accès; Modèle; Partenariat; Pôle d'innovation; Rôle des universités; Université

Gestión universitaria de la innovación social promovida desde espacios académicos relacionados con el emprendimiento, la investigación y la proyección social - Jurado-Paz, Irina Margarita; Morán-Vallejo, Michael Alexander (Revista de Investigación, Desarrollo e Innovación, 2019)
This article shows the diagnosis of the Interdisciplinary Rural Internship Program, PIRI, held in a university institution in order to identify elements to improve its implementation. The research is descriptive, with a mixed approach, where surveys and interviews were used to collect information. A sample of 214 students was considered, belonging to different programs of the Autonomous University Corporation of Nariño. The results indicate significant contributions from PIRI to the institutions and to the students who have participated in the program. PIRI is used in an educational space for students to develop skills and apply their knowledge on issues related to social innovation. However, there are also difficulties such as the low number of participants, together with the lack of clear procedures that allow an adequate articulation of the entities linked to PIRI. In this sense, a model was formulated to facilitate the university management of social innovation in the institution under study, which articulates the dependencies of entrepreneurship, research and social projection, so that the benefits are oriented both to the university community and to the territories.
Number: 2
Keywords: Amérique latine; Colombie; Innovation sociale; Libre accès; Rôle des universités

First domino tile in the social innovation process: Idea creation of university students - Yıldırım, Nihan; Ansal, Hacer (2016 Portland International Conference on Management of Engineering and Technology (PICMET), 2016)
Interrelations between creativity, innovativeness and entrepreneurial skills of individuals have long been discussed in the literature. Due to the challenges regarding their measurement, most studies focused on the intentions rather than the outcomes. The idea generation that requires creativity is the first stage of social innovation. The young population's creative potentials in participating social innovation practices deserve a special attention as they play a critical role in the innovativeness and entrepreneurship of societies. This study aims to explore the factors that determine the creative intentions of university students that are important in generating social innovation projects. A structured survey based on the literature was conducted among 600 management and engineering students from 3 universities from the different percentiles of the Entrepreneurial and Innovative University Index for 2012 of the Turkish Ministry of Science, Industry and Technology. The survey included questions on the demographic characteristics, environmental factors, motivators, university/institutional context, perceptions and creative thinking attitudes. By conducting reliability and factor analysis, accuracy and validity of data is tested and the impact factors were identified. Findings reveal that visionary attitude, curiosity, exploration and learning, attitude for own creativity, self-esteem, perception about the learnability of creativity, university and social environment are components of creative thinking intentions of students and some of these factors vary by year of study and university.
Keywords: Entrepreneuriat; Europe; Innovation sociale; Réservé UdeM; Rôle des universités; Université

Strengthening social innovation in higher education institutes - an organizational change process involving staff and students - Prantl, Judith; Freund, Susanne; Kals, Elisabeth (Social Enterprise Journal, 2021)
Purpose In recent decades, higher education institutes (HEIs) have come under pressure to cooperate with society as a whole. This shift towards an increased focus on third mission and social innovation activities implies a substantial organizational change process for many HEIs, as they need to initiate both structural and cultural changes. This paper provides guidance for such change processes by examining the views and attitudes of academic and administrative staff, as well as students within the HEIs over a period in which the HEIs increase their focus on social innovation. Design/methodology/approach The study uses a longitudinal quantitative approach consisting of a survey of administrative and academic staff, as well as students at two German HEIs. The authors studied members' attitudes towards third mission and social innovation activities (N = 3470). Findings Results suggest that the university members' attitudes towards third mission and social innovation are positive but change to some extent over time. Different aspects shape the attitudes within the three groups (administrative staff, academic staff and students). Furthermore, attitudes vary among academic employees who are involved in the process and those who are not. Practical implications The findings provide useful information for university managers and anyone aiming to promote social innovation at HEIs. Originality/value The study examines how attitudes of university members change whenever social innovation takes place at HEIs. This study includes data on the participation and empowerment of all HEI members in view of the important role that HEIs can play as supporters of social innovation.
N'AVONS PAS ACCÈS
Keywords: Innovation sociale; Rôle des universités; Université

The Landscape of Social Innovation in Canadian Universities: An Empirical Analysis - Milley, Peter; Szijarto, Barbara; Bennett, Kristen (Canadian Journal of Nonprofit and Social Economy Research, 2020)
La dernière décennie a été marquée par une croissance mondiale du nombre d’initiatives d’innovation sociale lancées dans le secteur universitaire. Ces initiatives visent à résoudre des problèmes sociaux complexes et à induire des changements institutionnels et systémiques. Cette poussée de l’activité d’innovation sociale se produit sans une base de connaissances empiriques bien développée. Nous y contribuons en fournissant une description et une analyse complètes de toutes les initiatives d’innovation sociale auxquelles participe le secteur universitaire canadien, de leurs caractéristiques et du paysage qu’elles constituent. Résultats notables: près de la moitié des 96 universités canadiennes sont associées à au moins une initiative; de nombreuses initiatives sont interdisciplinaires et mettent l’accent sur la résolution de problèmes en collaboration avec des secteurs extérieurs à l’université; Les agences gouvernementales et les fondations caritatives sont les sources de financement les plus courantes. Les résultats suggèrent: il existe un potentiel de croissance de l’innovation sociale dans le secteur; il y a moins de liens internes et de regroupement d’initiatives que ne le recommande la théorie de l’innovation; l’accent mis sur la collaboration extérieure rejoint la «troisième mission» des universités, qui existe depuis longtemps, mais les innovateurs sociaux ont des objectifs, des méthodes et des processus distincts pour mener à bien cette mission. Nous concluons avec les orientations pour les recherches futures. Keywords / Mots clés: Universities; Higher education; Social innovation; Community engagement; Service mission; Social change; Canada / Universités; Établissements d’enseignement supérieur; Innovation sociale; Engagement communautaire; Mission de service; Changement social; Canada
Number: 1
Keywords: Canada; Innovation sociale; Libre accès; Rôle des universités; Université

Space configurations for empowering university-community interactions - Dorland, Jens; Clausen, Christian; Jørgensen, Michael Søgaard (Science and Public Policy, 2019)
Some see universities as a possible source of solutions to enable a sustainable transition and overcome societal challenges. Findings from three multisite case studies of Desis Labs, FabLabs, and Science Shops shed light on how universities can help empower communities and solve societal challenges locally. Adopting a sociotechnical and flat relational perspective inspired by science and technology studies (STS), we focus on the material and spatial aspects of how these spaces are configured, thereby ensuring practical relevance for policy makers and practitioners. Applying an analytical generalization methodology, we condense the qualitative data into a typology of three ideal space-types (i.e. affording, mediating, and impact-oriented) that represent specific configurations of actors, researchers, students, communities, spaces, infrastructure, equipment, facilitators, etc. The ideal space-types empower communities in different ways, require different resources to create and operate, and translate differently into specific local contexts.
Number: 5
Keywords: Communauté d'innovation; Laboratoire vivant; Méthodes; Réservé UdeM; Rôle des universités; Université

Universities, inclusive development and social innovation: an international perspective - Brundenius, Claes; Göransson, Bo; Mello, Jose Manoel Carvalho de (Springer, 2017)
This book examines the ways in which universities can play a crucial role in inclusive development, social innovation and social entrepreneurship. It aims to prove the importance of inclusive development and inclusive innovation on economic growth and demonstrate the ways in which universities can be pioneers in this area through initiatives in social responsibility and social innovation. For example, providing access to a university education without discrimination of race, gender, income status, or other factors would help to diminish the increasing income differentials currently being experienced in many countries, especially in the developing world. The research and studies included in this book provide insight into possible actions that can be taken by universities and public and private shareholders in inclusive development, social innovation, social entrepreneurship and overall regional economic and social development.
Keywords: Développement inclusif; Développement social; Entrepreneuriat social; Innovation inclusive; Innovation sociale; Inégalités; Réservé UdeM; Rôle des universités; Université

University Medialabs: New Learning Spaces for Educational Innovation - Almaraz-Menéndez, Fernando; Martín-García, Teresa; López-Esteban, Carmen (Journal of Strategic Innovation and Sustainability, 2021)
Higher Education Institutions, like many other organizations, are facing pressure from the development of digital technologies as a push towards the digitization of their activities and towards a type of change that some describe as disruptive and that forces them to review their processes and structures. This article describes the case of the medialab of the University of Salamanca, MEDIALAB USAL, as an experience of new learning space in higher education. Its origin is explained from the experiences of citizen technology laboratories and experimental laboratories at the point of intersection between Art, Science and Technology. Its structure and working methods are explained, and its activities are illustrated through the description of four educational innovation projects based on different digital technologies: a mathematics didactics project using AppInventor, Wikipedia as a tool for knowledge generation, Arduino for innovation in the teaching of Fine Arts and a university Hackathon as an activity to introduce students to social and entrepreneurial innovation processes.
Number: 4
Keywords: Collaboration; Durabilité; Europe; Innovation pédagogique; Innovation sociale; Laboratoire vivant; Libre accès; Living Labs; Rôle des universités; Technologies; numérique

University Social Responsibility during the COVID-19 Pandemic: Universities’ Case in the BRICS Countries - Rababah, Abedalqader; Nikitina, Natalya I.; Grebennikova, Veronica M.; Gardanova, Zhanna R.; Zekiy, Angelina O.; Ponkratov, Vadim V.; Bashkirova, Nadezhda N.; Kuznetsov, Nikolay V.; Volkova, Tatyana I.; Vasiljeva, Marina V.; Ivleva, Marina I.; Elyakova, Izabella D. (Sustainability, 2021)
University social responsibility (USR) is an important assessment criterion of the QS Stars. In the context of the COVID-19 pandemic, the social orientation of universities as intellectual leaders in the development of society gains particular importance. The research purpose is to analyze the impact of the COVID-19 pandemic on the university activity directions in the framework of strategies (USR). An empirical assessment of the level and complementary factors of USR in the BRICS countries (Brazil, Russia, India, China, and South Africa) was conducted, using the method of integral and expert assessment. Grounded on scoring according to the principal component analysis, the structure of the factors of the USR development in the BRICS countries was determined. Multifactor regression modeling allowed substantiating the priority of factors stimulating the development of USR in the BRICS countries in modern conditions and arguing the main barriers to introducing the concept of social responsibility into university activities and expanding the stakeholders’ circle in it. The research results showed that the university management creativity, effective communication with the public and stakeholders, the quality of the educational process and the development of scientific activities stimulate USR development in the BRICS countries and should be used as the basis for the strategic planning of activities in the context of the continuing COVID-19 pandemic. Conceptual trends in the USR development can be useful for universities in the studied countries when adapting strategic development plans regarding the social needs of modern society.
Number: 13 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Libre accès; Responsabilité sociale; Rôle des universités; Université

Unpacking the role of universities in the emergence, development and impact of social innovations – A systematic review of the literature - Bayuo, Blaise Booponoyeng; Chaminade, Cristina; Göransson, Bo (Technological Forecasting and Social Change, 2020)
Widening income and knowledge inequalities have led to growing expectations for universities to integrate social innovation in their core missions as a response to societal problems. This systematic review of literature provides an overview of the state-of-the-art of knowledge on the role of the university in enabling social innovation through its missions of teaching, research and third mission. It also identifies knowledge gaps in the field. A bibliometric approach wasused to identify and analyze books, journal articles and reports examining factors driving social innovation activities at universities, organizational and insitutional change to accommodate such activities as well as their impact. The review reveals that the literature on university engagement in socially-oriented activities as part of the third mission of the university is conceptually well developed and a growing field of inquiry. It also points to gaps in the knowledge base; relatively few studies address issues related to institutional change and incentive structures that influences the ability of universities to engage in social innovation. Likewise, impact studies on social innovation activities at universities are scarce. Further research that builds an impact measurement framework would support the process of integrating social innovation activities in the three missions of the university.
Num Pages: 1 Place: New York, United Kingdom Publisher: Elsevier Science Ltd.
Keywords: Innovation sociale; Mesure d'impact; Recherche; Réservé UdeM; Rôle des universités; Université

Why do universities have little systemic impact with social innovation? An institutional logics perspective - Cinar, Ridvan; Benneworth, Paul (Growth & Change, 2021)
Social innovation has been increasingly regarded as an instrument through which transformative structural change, necessary to address grand societal challenges can be achieved. Social innovations are encouraged by the emergence of innovation systems that support changes not exclusively driven by a techno-economic rationality. In the context of this special issue, there has been both little understanding of social innovation systems within mainstream innovation ecosystem approaches and little analysis of the roles played by universities in social innovation systems. We here focus on the institutional complexity of universities and their field-level dynamics as serving as a potential break on the institutionalisation of social innovation. To deepen our understanding of this, we utilise a literature around institutional logics to foreground characteristics of organisational fields with regard to social innovation. Drawing on empirical data gathered in two public universities located in different countries, we show that in one case the potential of social innovation is undermined by two dominant institutional logics, in the other its permeation across the organisational field is seriously challenged by a more powerful dominant logic. The institutional logic approach is useful to highlighting the barriers to building productive innovation ecosystems incorporating social considerations, and helps to explain the persistent difficulties in reframing ecosystems approaches to reflect wider societal dynamics.
Number: 2
Keywords: Réservé UdeM; Rôle des universités

¿Son las universidades socialmente responsables? - Valle, Maria Belén Arias; Berbegal-Mirabent, Jasmina; Marimon-Viadiu, Frederic (education policy analysis archives, 2021)
The importance of university social responsibility (USR) is given by the commitment assumed by the university towards its stakeholders. This study aims at providing new insights on this topic, by analyzing the level of performance in USR that universities communicate. To this end, a structured procedure in five phases is proposed, analyzing elements of the strategic direction and considering the use of USR indicators which are grouped in the four main areas of impact (organizational, educational, cognitive and social). To do this, a qualitative approach has been followed, supported by the use of text analysis software as well as by frequency and spider diagrams. To illustrate its use and the type of analysis it allows, the procedure is applied to the case of the Catalan higher education system, presenting the results at different levels. The study ends with the discussion of the implications, a list of recommendations and suggestion for future works.
Number: January - July Accès libre
Keywords: Europe; Libre accès; Rôle des universités

Universities as Drivers of Social Innovation: Theoretical Overview and Lessons from the "campUS" Research - Fassi, Davide; Landoni, Paolo; Piredda, Francesca; Salvadeo, Pierluigi (Springer, 2020)
Reviews the social role of universities in the urban context Covers themes and models of major interest Explains how to ensure a legacy of grassroots initiatives
Keywords: Mise en valeur; Réservé UdeM; Rôle des universités

Innovations in Multistakeholder Partnerships for Sustainable Development: Fostering State–University–Community Nexus - Shaban, Abdul; Narnaware, Prashant B. (People-Centered Social Innovation, 2019)
This chapter shows that there is a possibility of fostering an enabling and innovative multistakeholder partnership for creating sustainable impact and transformative change with local communities. It argues that the collaborative efforts among district administration, educational institutions and civil society groups in supporting innovation and entrepreneurship can play an extremely important role in livelihood security and empowerment of marginalized sections. The chapter outlines the transformation of a marginalized and underdeveloped district of India. It presents a background of the district with a focus on farmers’ distress and discusses the mode of organization of elites and marginalized peoples under welfare and neoliberal regimes. The chapter also outlines the impact that state–university engagement on the communities. The neoliberal regime made the elite-based cooperatives ineffective, as they came under mismanagement and overexploitation by those in power. Neoliberal reform introduced a new vulnerability among Indian farmers, especially in certain states, such as Maharashtra.
Num Pages: 16
Keywords: Asie; Réservé UdeM; Rôle des universités

Rapid Community Innovation: a Small Urban Liberal Arts Community Response to COVID-19 - Talmage, Craig Allen; Annear, Christopher; Equinozzi, Kate; Flowers, Kathleen; Hammett, Grace; Jackson, Amy; Kingery, Julie Newman; Lewis, Robin; Makker, Kirin; Platt, Audrey; Schneider, Travis; Turino, Caroline (International Journal of Community Well-Being, 2021)
Stories of community resilience and rapid innovation have emerged during the global pandemic caused by COVID-19. As communities, organizations, and individuals have had to shift modalities during the pandemic, they have identified ways to sustain community well-being. Prior to COVID-19, colleges and universities were hailed as anchors of economic and social resilience and well-being for communities of place. In this light, this commentary highlights stories of rapid community innovation occurring at Hobart & William Smith Colleges in the Finger Lakes region of New York. A series of vignettes are presented showcasing lessons and on-going questions regarding rapid pivots, community values, and diversity and inclusion during (and after) the pandemic. Overall, these insights can inform future local collaborative development efforts post-COVID-19 between colleges/universities and their local community.
Number: 3
Keywords: Réservé UdeM; Rôle des universités; États-Unis

The social impact of universities: assessing the effects of the three university missions on social engagement - Carl, Johannes; Menter, Matthias (Studies in Higher Education, 2021)
Whereas the economic impact of universities is undisputed, the social impact of universities remains vague. The purpose of this paper is to examine whether and how universities influence firms’ social engagement. Based on survey data of more than 7,000 German firms, our results reveal that universities positively affect firms’ social engagement mainly through teaching activities. Hence, our findings give impetus to a reinforcement of the university mission ‘teaching’ as a central lever for social change and increased social awareness as well as to a reorientation of the third university mission toward social needs. This paper thereby contributes to our understanding of the changing missions and values of universities and adds to the literature by exploring the underlying mechanisms of the social impact of universities. We conclude the paper with fruitful future avenues of research.
Number: 5
Keywords: Europe; Réservé UdeM; Rôle des universités

Universities as change agents in resource-poor local settings: An empirically grounded typology of engagement models - Petersen, Il-haam; Kruss, Glenda (Technological Forecasting & Social Change, 2021)
University-community engagement is emerging as an important channel for social innovation, requiring universities to act as change agents in their local settings. The role of change agent presents new challenges for universities as it requires going beyond institutional borders to collaborate with non-traditional partners such as informal enterprises, and to stimulate and support innovation that may be seen as relevant to a given local setting only. Universities are thus grappling with finding suitable mechanisms and models for engaging in institutional contexts that are vastly different from traditional formal university- and firm-based settings. Based on empirically rich case study research in a South African township, the paper presents new conceptual insights on how universities can catalyse social change in resource-poor local settings through strategically selecting mechanisms and models of engagement that align with locally-embedded institutions, practices and needs. Four types of engagement models are identified, each relate to different models of entrepreneurship and innovation and thus different modes of learning. The typology distinguishes between dominant, traditional knowledge transfer models, and emergent, socially responsive models that show greater promise for promoting collective agency and effecting systemic social change. The typology can be used to assess current practice and inform future strategies.
Keywords: Afrique; Réservé UdeM; Rôle des universités

Co-Creation for Social Innovation in the Ecosystem Context: The Role of Higher Educational Institutions - Kumari, Richa; Kwon, Ki-Seok; Lee, Byeong-Hee; Choi, Kiseok (Sustainability, 2020)
This study examined the role of Higher Educational Institutions (HEIs) in promoting, creating, and sustaining social innovation. Recently, HEIs have extended their contribution beyond the traditional function of teaching and research to perform in socio-economic problem-solving. Considering the increasing trends of higher education involvement in social innovation practices, this study tries to examine the tools such as learning processes and systemic thinking approach that could be helpful to align the function and responsibilities of HEIs towards social innovation. The objective is to develop a theoretical understanding of the "co-creation for social innovation" concept and to understand the functions and activities of HEIs that can contribute to this process. To promote co-creation for social innovation, HEIs should actively encourage collaborative learning tools that focus on open platforms for collective action and systemic change that help them to engage with society and strengthen their collaboration with social actors. Different activities such as mutual learning and knowledge diffusion using a transdisciplinary approach, technology-based learning and collaboration, and relational transformation are key enablers that can promote social innovation.
Number: 1 Place: Basel Publisher: Mdpi WOS:000521955600307
Keywords: Co-création; Libre accès; Rôle des universités

Knowledge transfer for frugal innovation: where do entrepreneurial universities stand? - Fischer, Bruno; Guerrero, Maribel; Guimón, José; Schaeffer, Paola Rücker (Journal of Knowledge Management, 2020)
Frugal innovation has gained prominence based on its potential contribution to sustainable development and the new opportunities that it offers to low-income customers. This paper aims to analyse the strategic knowledge transfer practices implemented by an entrepreneurial university for fostering frugal innovations within an emerging economy. Design/methodology/approach This study adopted a case study methodological approach. The selected case was the University of Campinas (Unicamp), one of the leading universities in Brazil in terms of research quality and technology transfer. The study built upon 14 interviews with key informants and secondary sources of data (official and public documents). Findings The findings highlight the multidimensional dynamics of frugal innovations arising from university–industry relationships. Key dimensions considered include the internal capabilities of universities to foster frugal innovations and connect them to markets, the surrounding innovation ecosystems in which the university is embedded and the overarching institutional framework. Research limitations/implications The analysis of strategic management practices for frugal innovation requires an evolutionary perspective, but the findings lacked sufficient longitudinal information for a formal evaluation. Also, as our empirical analysis is based on an in-depth case study of one university, further validation in other contexts would be necessary. Practical implications This study offers new insights regarding the effectiveness of university-business collaboration partnerships for developing frugal innovations in emerging economies. Policymakers should promote societal programs enhancing the active participation of all agents involved in the entrepreneurial and innovation ecosystem. University managers should understand the challenges and the opportunities behind the adoption of an inclusive and societal orientation. Social implications By adopting frugal innovation practices, universities can enhance their contribution of meeting the United Nations’ Sustainable Development Goals. Originality/value The literature on frugal innovation has emphasized the importance of networking between different types of firms, NGOs and governments, but the role of universities in frugal innovation remains mostly unexplored. This study addresses this gap by exploring how entrepreneurial universities participate in frugal innovations to meet societal challenges.
Number: 2 Publisher: Emerald Publishing Limited
Keywords: Brésil; Innovation frugale; Réservé UdeM; Rôle des universités

Technology-transfer offices and academic open labs as different types of organizational intermediaries in science-society relationships - Mérindol, Valérie; Gallié, Emilie Pauline; Capdevila, Ignasi (Gestion 2000, 2018)
Cet article étudie les caractéristiques des structures de transfert technologique et des laboratoires d’innovation ouverte gérés par les universités et organismes de recherche. Il compare leurs rôles comme intermédiaires des relations science–entreprises en fonction des modes 2 et 3 de production des connaissances proposés par Etzkowitz & al (1997) et Carayannis & al (2009). Basée sur une comparaison de cas multiples en France, nous analysons leur rôle dans le développement des relations science-entreprise. Cet article identifie aussi les modes de coordination entre ces deux types d’intermédiaires. Dans certains cas, ils coordonnent leurs activités de manière ponctuelle alors que, dans d’autres cas, la complémentarité de leurs activités s’organise sur la durée.
Number: 2 Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 1 Publisher: Association de Recherches et Publications en Management
Keywords: Europe; France; Réservé UdeM; Rôle des universités

Universities and social innovation for global sustainable development as seen from the south - Arocena, Rodrigo; Sutz, Judith (Technological Forecasting and Social Change, 2021)
Potential contributions of universities to social innovation are explored with special attention to Southern countries. The normative guide is the notion of Sustainable Human Development understood as stressing the agency of least-advantaged sectors. The main challenges stem from decreasing sustainability and increasing inequality. Their impacts are highly dependent on how the tension between economic growth and environmental protection is managed. Improving actual perspectives demands harnessing advanced knowledge to foster inclusive and frugal innovation. For this to occur, universities need to be main actors. The context in which they act is analyzed with reference to the National Systems of Innovation conceptualization. Possible evolutions of universities as agents of social innovation are discussed with the aid of the Multi-Level Perspective. The importance of the Southern experience of innovating in scarcity conditions is highlighted and illustrated with the specific experience of a Latin American university. The cooperation of universities with weak social actors in ways that involve advanced knowledge appears as a key theoretical issue and as a difficult practical problem for the effective engagement of universities in social innovation. The diverse issues that such engagement needs to integrate conform an ambitious research program, of which the paper aims at giving a first glimpse.
Num Pages: 1 Place: New York, United Kingdom Publisher: Elsevier Science Ltd.
Keywords: Amérique latine; Développement Durable-Responsabilité Sociale (DD-RS); Innovation sociale; Réservé UdeM; Rôle des universités

Quelle structuration de la démarche de Développement Durable-Responsabilité Sociale (DD-RS) à l’université ? L’exemple des universités françaises - Petitjean, Jean-Luc; Ory, Jean-Francis; Côme, Thierry (Recherches en Sciences de Gestion, 2021)
L’article est basé sur une enquête portant sur la structuration de la démarche de développement durable et responsabilité sociale (DD-RS) dans les universités françaises. Il s’appuie sur la théorie de la structuration et la Théorie Néo-Institutionnelle pour construire un cadre conceptuel à la structuration de cette mission. Ce dernier est confronté à la pratique des établissements et débouche sur une typologie fondée sur le rôle de l’implication politique, de la culture du pilotage et des isomorphismes. La discussion autour de cette typologie, à partir d’une ACM montrant l’existence de groupes homogènes d’universités quant à leur structuration d’une démarche DD-RS, permet d’affiner le rôle de chacun des facteurs du modèle conceptuel.
Number: 3 Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 0 Publisher: ISEOR
Keywords: Développement Durable-Responsabilité Sociale (DD-RS); Réservé UdeM; Rôle des universités; Théorie Néo-Institutionnelle

From Research to Numbers: Role of Universities in Social Innovation - Cunha, Jorge; Ferreira, Carla; Araújo, Madalena; Benneworth, Paul (Innovations in Industrial Engineering, 2022)
Commonly, social innovation is defined as new ideas proposals to the needs of humans. However, there is a lack of a well-definition comprehensive leading the fragmentation of field research. On the other hand, the contribution of universities for social innovation development is still less investigated. In this sense, this study intends to explore interrelations between universities and social innovation in relation to different lines of investigation employed. For this, a content analysis was applied to results obtained by Cunha et al. [1]. Five categories of analysis were defined. Findings revealed that there are a number of studies that applied qualitative research to investigate practical examples of social innovation inside of universities and few empirical studies. A link among keywords social innovation, higher education, and social entrepreneurship was found. Furthermore, the analysis showed that there is not a leader country but a distribution across several countries, where Spain and United Kingdom stand out. Thus, this result suggests that it would be helpful to develop an instrument to measure academics’ engagement with social innovation research and practice. In addition, this research contributes to current knowledge regarding the role of universities in social innovation model, providing new theoretical and practical insights of investigation.
N'AVONS PAS ACCÈS
Keywords: Europe; Rôle des universités

Integrating Social Innovation into the Curriculum of Higher Education Institutions in Latin America: Insights from the Students4Change Project - Unceta, Alfonso; Guerra, Igone; Barandiaran, Xabier (Sustainability, 2021)
In the last two decades, social innovation (SI) and social entrepreneurship (SE) have gained relevance and interest within the framework of academia at international level. Higher education institutions (HEIs) are key players in promoting innovation and social entrepreneurship initiatives that respond to multifaceted challenges. They support strategies on the basis of the strengthening of participation, collaboration, and cooperation with society and its local communities. However, the approach of Latin American universities to SI and SE has been very uneven in the way they have understood them, integrated them into academic programmes, and transferred knowledge to society. On the basis of the experience of the Students4Change project, we sought to understand the role of Latin American HEIs in promoting social innovations by analysing the experiences of 10 participating universities to formalise a pedagogical programme on SI and SE in their institutions. The results suggest that there is still a need to formalise an academic syllabus that is speciﬁcally designed to promote social innovations and to train universities in this endeavour. This paper contributes to the identiﬁcation of the main levers of change, strengths, and challenges that Latin American universities face to institutionalise SI and SE in their contexts.
Number: 10
Keywords: Amérique latine; Libre accès; Rôle des universités

Social Innovation at Technical Universities – State of the Art - Berg, Julia; Leicht-Scholten, Carmen (Proceedings of ISPIM Conferences, 2021)
This paper presents the state of the art in promoting social innovation at five leading technical universities in Europe. We assess how these leading technical universities implement social innovation in their strategies, teaching, and research. The results show that all universities highlight the importance of finding solutions to global challenges and addressing Responsible Research and Innovation (RRI) as a fundamental university strategy for example by promoting social innovation. Moreover, all address the universities’ need to contribute to sustainability and the Sustainable Development Goals. However, social innovation does not play an important role in research and teaching as the results show that social innovation has so far been little addressed in research and teaching. Based on the political framework in the five European countries, we draw up conclusions for technical universities
N'AVONS PAS ACCÈS
Keywords: Europe; Rôle des universités

Contribution of Higher Education Institutions to Social Innovation: Practices in Two Southern European Universities - Monteiro, Sílvia; Isusi-Fagoaga, Rosa; Almeida, Leandro; García-Aracil, Adela (Sustainability, 2021)
The interactions between the higher education sector and society and industry have been attracting increased attention in terms of ways to develop social innovation solutions to societal problems. Despite calls from politicians and the existence of some guidelines, we know little about how higher education could incorporate social innovation activities into its structure and missions. This study examines some practice experiences in two southern European public universities in Portugal and Spain. We show that the third mission of universities, which includes social innovation, is both linked to the first two missions of teaching and research, depending on the university’s historical and social context. The high dependence of higher education institutions on economic returns increases the importance of political action to drive the development of social innovation activities. This conditioning factor seems to be intrinsic to some of the barriers that have been identified, such as lack of legitimization and recognition of social innovation practices at the formal governmental level.
Number: 7 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Europe; Libre accès; Rôle des universités

Digital Innovation during COVID-19: Transforming Challenges to Opportunities - Yu Chen; Roldan, Malu (Communications of the Association for Information Systems, 2021)
The coronavirus disease of 2019 (COVID-19) swiftly changed almost all aspects of our lives and society. In this paper, we depict course adjustments that we made to an undergraduate digital innovation course project, called Innovation Farm (IF), in response to the pandemic. Designed as an in-person course project, IF requires students to create AIpowered Android apps to address important social issues. As stay-at-home orders came into effect in March, 2020, we shifted the course to the online modality refocused its student topics to address social issues that COVID-19 has engendered. Accordingly, we also discuss three challenges that we faced and the strategies we employed to cope with them; namely, framing students' social innovation topics in the COVID-19 context, using virtual studios for online groupwork, and hosting a virtual pitch competition. Surprisingly, these strategies not only addressed the challenges but also created unintended benefits and opportunities. We hope to encourage educators to consider the possibilities in transforming challenges to opportunities during these unprecedented times.
Keywords: Réservé UdeM; Rôle des universités; États-Unis

New Challenges in Universities: Teaching Social Entrepreneurship - Lam-Lam, Suisin; Ahumada-Tello, Eduardo; Plascencia-López, Ismael; Ovalle-Osuna, Oscar Omar; Virginia Barragán-Quintero, Reyna; Evans, Richard David; Soria-Barreto, Karla (2019 IEEE Technology Engineering Management Conference (TEMSCON), 2019)
This study analyses the importance of teaching social entrepreneurship in state universities. A survey was applied to university students to find out if personality traits are related to the characteristics of social entrepreneurship. This was achieved through Alpha Cronbach and Pearson/Spearman correlation analysis. The results show that students have the personality traits to become social entrepreneurs. However, social entrepreneurship courses are not taught in universities of Tijuana city. Therefore, it is strongly suggested to teach social entrepreneurship in universities of the city and the state because students possess social entrepreneurship traits and are interested in the subject.
Keywords: Amérique latine; Réservé UdeM; Rôle des universités

The potential of ICT-enabled social innovation - Kedmenec, Irena; Detelj, Kristina; Kadoić, Nikola (2019 42nd International Convention on Information and Communication Technology, Electronics and Microelectronics (MIPRO), 2019)
Although social innovation is an old paradigm, social innovation courses appeared in the curricula in the approximately last ten years. By doing so educational institutions acknowledged the existence of new approaches to obstacles that the world is facing. The courses regarding the social innovations give the students valuable knowledge and skills related to solving different social problems, increasing the motivation for being active in the society, and raising awareness about specific topics that need attention. An important role in implementing social innovation have ICT technologies. The role of the ICT is multiple: (1) administrative (members of the certain social initiative collaborate on the project through different ICT tools that enable communication and information organization), (2) disseminative and educational (the topic of the social initiative is disseminated through different tools and social media), and sometimes (3) topical (it the topic of social innovation project is directly connected to specific ICT technology). Based on the roles that the ICT takes upon in the process of social innovation implementation, the authors present ICT solutions that could be included in the realization of a social innovation course for business students at the graduate level.
ISSN: 2623-8764
Keywords: Relations industrielles; Réservé UdeM; Rôle des universités

Empowering social innovators through collaborative and experiential learning - Pappas, Ilias O.; Mora, Simone; Jaccheri, Letizia; Mikalef, Patrick (2018 IEEE Global Engineering Education Conference (EDUCON), 2018)
Educating social innovators in higher education is of great importance as many societal challenges exist. This study combines experiential learning with ICT tools to provide students with the needed competences and experiences to solve societal challenges. We employ this approach in an innovative course, named Experts in Teamwork (EiT), which follows the experiential learning cycle. The participants of this study are undergraduate students interested to learn how they can solve societal challenges. Specifically, 26 students with various background and nationalities participated. A collaborative platform was developed that supports teamwork and cooperation, as well as the social innovation process. The findings show that this approach can influence positively learning outcomes and increase students' engagement and motivation with both social innovation and the learning process. Also, students' creativity was increased leading to the development of better solutions. The overall outcomes contribute to theoretical and practical development, to allow educators to take appropriate measures to enhance students' learning experience and foster social innovation through ICT.
ISSN: 2165-9567
Keywords: Réservé UdeM; Rôle des universités

The role of universities in the development of public sector innovations - Polbitsyn, Sergei N. (The Innovation Journal, 2021)
Studies on public sector innovation often treat this type of innovation as something that emerges within public sector organizations. However, innovation theory argues that external sources of innovation are more fruitful sources of ideas. We claim that universities must be treated as a mandatory element in public sector innovation. This paper is aimed at clarifying the place of public sector innovation in the classification of innovations currently used in the literature. It also seeks to conceptualize an approach for future research on the topic. Our primary goal is to identify the role of different actors in the development of public sector innovation. We analyze the advantages and disadvantages of different forms of university involvement in public sector innovation. The paper consists of two parts. The first defines concepts of innovation in general and public sector innovation viewed as a variation on social innovation. The second is dedicated to an analysis of the experience of Russian universities in enhancing collaboration between actors in the public innovation system.
Number: 1 Num Pages: 1-19 Place: Ottawa, Canada Publisher: The Innovation Journal
Keywords: Asie; Réservé UdeM; Rôle des universités

A Hub-based University Innovation Model - Prieto Mejia, Samuel; Montes Hincapie, Juan Manuel; Taborda Giraldo, John Alexander; Prieto Mejia, Samuel; Montes Hincapie, Juan Manuel; Taborda Giraldo, John Alexander (Journal of technology management & innovation, 2019)
This article uses a conceptual approach to propose an innovation model for regional universities. It demonstrates that the traditional university encounters several obstacles that hinder its full integration into the development of its respective region and explains why currently known models cannot adapt to regions that have deficient relationships with the government and lack an entrepreneurial base. The new model is based on a structure composed of units called “innovation hubs” and incorporates social innovation, thus permitting the university to become integrated into the regional innovation ecosystems. The Magdalena University in Colombia was used as a reference in developing the model. Keywords: hub; social innovation; university innovation models; regional innovation ecosystems
Publisher: Universidad Alberto Hurtado. Facultad de Economía y Negocios
Keywords: Amérique latine; Colombie; Innovation sociale; Libre accès; Modèle; Partenariat; Pôle d'innovation; Rôle des universités; Université

First domino tile in the social innovation process: Idea creation of university students - Yıldırım, Nihan; Ansal, Hacer (2016 Portland International Conference on Management of Engineering and Technology (PICMET), 2016)
Interrelations between creativity, innovativeness and entrepreneurial skills of individuals have long been discussed in the literature. Due to the challenges regarding their measurement, most studies focused on the intentions rather than the outcomes. The idea generation that requires creativity is the first stage of social innovation. The young population's creative potentials in participating social innovation practices deserve a special attention as they play a critical role in the innovativeness and entrepreneurship of societies. This study aims to explore the factors that determine the creative intentions of university students that are important in generating social innovation projects. A structured survey based on the literature was conducted among 600 management and engineering students from 3 universities from the different percentiles of the Entrepreneurial and Innovative University Index for 2012 of the Turkish Ministry of Science, Industry and Technology. The survey included questions on the demographic characteristics, environmental factors, motivators, university/institutional context, perceptions and creative thinking attitudes. By conducting reliability and factor analysis, accuracy and validity of data is tested and the impact factors were identified. Findings reveal that visionary attitude, curiosity, exploration and learning, attitude for own creativity, self-esteem, perception about the learnability of creativity, university and social environment are components of creative thinking intentions of students and some of these factors vary by year of study and university.
Keywords: Entrepreneuriat; Europe; Innovation sociale; Réservé UdeM; Rôle des universités; Université

Academic Entrepreneurship and Community Engagement: Scholarship in Action and the Syracuse Miracle - Kingma, Bruce (Cheltenham, U.K. and Northampton, Mass.: Elgar, 2011)
Eleven papers explore research in entrepreneurship and community engagement in the context of Syracuse University's Scholarship in Action Model, which emphasizes sustainable campus-community entrepreneurial partnerships and applied research on the outcomes of these. Papers discuss the five keys to success in academic entrepreneurship; transforming a professional curriculum through engagement with practice–the Global Enterprise Technology Program at Syracuse University; tapping our fountain of youth–the guiding philosophy and first report on the Syracuse Student Startup Accelerator; Syracuse University Technology Commercialization Clinics; community development law and legal education; the Syracuse Miracle–inspiring entrepreneurs through conversations; the South Side Newspaper Project; bridging a traumatic past to an envisioned future–a case study of social entrepreneurship; inclusive entrepreneurship; the role of information and motivation in the process of innovation; and students serving as catalysts within a teacher education innovation.
Accès 1 usager à la fois sur ebook Central
Keywords: Communauté d'innovation; Engagement communautaire; Entrepreneuriat; Idéation; dialogue et maillage; Partenariat; Réservé UdeM; Rôle des universités; Transfert; Université; États-Unis

Strengthening social innovation in higher education institutes - an organizational change process involving staff and students - Prantl, Judith; Freund, Susanne; Kals, Elisabeth (Social Enterprise Journal, 2021)
Purpose In recent decades, higher education institutes (HEIs) have come under pressure to cooperate with society as a whole. This shift towards an increased focus on third mission and social innovation activities implies a substantial organizational change process for many HEIs, as they need to initiate both structural and cultural changes. This paper provides guidance for such change processes by examining the views and attitudes of academic and administrative staff, as well as students within the HEIs over a period in which the HEIs increase their focus on social innovation. Design/methodology/approach The study uses a longitudinal quantitative approach consisting of a survey of administrative and academic staff, as well as students at two German HEIs. The authors studied members' attitudes towards third mission and social innovation activities (N = 3470). Findings Results suggest that the university members' attitudes towards third mission and social innovation are positive but change to some extent over time. Different aspects shape the attitudes within the three groups (administrative staff, academic staff and students). Furthermore, attitudes vary among academic employees who are involved in the process and those who are not. Practical implications The findings provide useful information for university managers and anyone aiming to promote social innovation at HEIs. Originality/value The study examines how attitudes of university members change whenever social innovation takes place at HEIs. This study includes data on the participation and empowerment of all HEI members in view of the important role that HEIs can play as supporters of social innovation.
N'AVONS PAS ACCÈS
Keywords: Innovation sociale; Rôle des universités; Université

University Social Responsibility during the COVID-19 Pandemic: Universities’ Case in the BRICS Countries - Rababah, Abedalqader; Nikitina, Natalya I.; Grebennikova, Veronica M.; Gardanova, Zhanna R.; Zekiy, Angelina O.; Ponkratov, Vadim V.; Bashkirova, Nadezhda N.; Kuznetsov, Nikolay V.; Volkova, Tatyana I.; Vasiljeva, Marina V.; Ivleva, Marina I.; Elyakova, Izabella D. (Sustainability, 2021)
University social responsibility (USR) is an important assessment criterion of the QS Stars. In the context of the COVID-19 pandemic, the social orientation of universities as intellectual leaders in the development of society gains particular importance. The research purpose is to analyze the impact of the COVID-19 pandemic on the university activity directions in the framework of strategies (USR). An empirical assessment of the level and complementary factors of USR in the BRICS countries (Brazil, Russia, India, China, and South Africa) was conducted, using the method of integral and expert assessment. Grounded on scoring according to the principal component analysis, the structure of the factors of the USR development in the BRICS countries was determined. Multifactor regression modeling allowed substantiating the priority of factors stimulating the development of USR in the BRICS countries in modern conditions and arguing the main barriers to introducing the concept of social responsibility into university activities and expanding the stakeholders’ circle in it. The research results showed that the university management creativity, effective communication with the public and stakeholders, the quality of the educational process and the development of scientific activities stimulate USR development in the BRICS countries and should be used as the basis for the strategic planning of activities in the context of the continuing COVID-19 pandemic. Conceptual trends in the USR development can be useful for universities in the studied countries when adapting strategic development plans regarding the social needs of modern society.
Number: 13 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Libre accès; Responsabilité sociale; Rôle des universités; Université

Between Good Intentions and Enthusiastic Professors: The Missing Middle of University Social Innovation Structures in the Quadruple Helix - Benneworth, Paul; Cunha, Jorge; Cinar, Ridvan (Regional Helix Ecosystems and Sustainable Growth: The Interaction of Innovation, Entrepreneurship and Technology Transfer, 2020)
This chapter considers the role of universities in stimulating social innovation, and in particular the issue that despite possessing substantive knowledge that might be useful for stimulating social innovation, universities to date have not been widely engaged in social innovation activities in the context of Quadruple Helix developmental models. We explain this in terms of the institutional logics of engaged universities, in which entrepreneurial logics have emerged in recent decades, that frame the desirable forms of university-society engagement in terms of the economic benefits they bring. We ask whether institutional logics could explain this resistance of universities to social innovation. Drawing on two case studies of universities sincerely committed to supporting social innovation, we chart the effects of institutional logics on university-supported social innovation. We observe that there is a “missing middle” between enthusiastic managers and engaged professors, in which four factors serve to undermine social innovation activities becoming strategically important to HEIs. We conclude by noting that this missing middle also serves to segment the operation of Quadruple Helix relationships, thereby undermining university contributions to societal development more generally.
Keywords: Innovation sociale; Quadruple helix approach; Réservé UdeM; Rôle des universités; Université

Gestión universitaria de la innovación social promovida desde espacios académicos relacionados con el emprendimiento, la investigación y la proyección social - Jurado-Paz, Irina Margarita; Morán-Vallejo, Michael Alexander (Revista de Investigación, Desarrollo e Innovación, 2019)
This article shows the diagnosis of the Interdisciplinary Rural Internship Program, PIRI, held in a university institution in order to identify elements to improve its implementation. The research is descriptive, with a mixed approach, where surveys and interviews were used to collect information. A sample of 214 students was considered, belonging to different programs of the Autonomous University Corporation of Nariño. The results indicate significant contributions from PIRI to the institutions and to the students who have participated in the program. PIRI is used in an educational space for students to develop skills and apply their knowledge on issues related to social innovation. However, there are also difficulties such as the low number of participants, together with the lack of clear procedures that allow an adequate articulation of the entities linked to PIRI. In this sense, a model was formulated to facilitate the university management of social innovation in the institution under study, which articulates the dependencies of entrepreneurship, research and social projection, so that the benefits are oriented both to the university community and to the territories.
Number: 2
Keywords: Amérique latine; Colombie; Innovation sociale; Libre accès; Rôle des universités

Universities, inclusive development and social innovation: an international perspective - Brundenius, Claes; Göransson, Bo; Mello, Jose Manoel Carvalho de (Springer, 2017)
This book examines the ways in which universities can play a crucial role in inclusive development, social innovation and social entrepreneurship. It aims to prove the importance of inclusive development and inclusive innovation on economic growth and demonstrate the ways in which universities can be pioneers in this area through initiatives in social responsibility and social innovation. For example, providing access to a university education without discrimination of race, gender, income status, or other factors would help to diminish the increasing income differentials currently being experienced in many countries, especially in the developing world. The research and studies included in this book provide insight into possible actions that can be taken by universities and public and private shareholders in inclusive development, social innovation, social entrepreneurship and overall regional economic and social development.
Keywords: Développement inclusif; Développement social; Entrepreneuriat social; Innovation inclusive; Innovation sociale; Inégalités; Réservé UdeM; Rôle des universités; Université

The Landscape of Social Innovation in Canadian Universities: An Empirical Analysis - Milley, Peter; Szijarto, Barbara; Bennett, Kristen (Canadian Journal of Nonprofit and Social Economy Research, 2020)
La dernière décennie a été marquée par une croissance mondiale du nombre d’initiatives d’innovation sociale lancées dans le secteur universitaire. Ces initiatives visent à résoudre des problèmes sociaux complexes et à induire des changements institutionnels et systémiques. Cette poussée de l’activité d’innovation sociale se produit sans une base de connaissances empiriques bien développée. Nous y contribuons en fournissant une description et une analyse complètes de toutes les initiatives d’innovation sociale auxquelles participe le secteur universitaire canadien, de leurs caractéristiques et du paysage qu’elles constituent. Résultats notables: près de la moitié des 96 universités canadiennes sont associées à au moins une initiative; de nombreuses initiatives sont interdisciplinaires et mettent l’accent sur la résolution de problèmes en collaboration avec des secteurs extérieurs à l’université; Les agences gouvernementales et les fondations caritatives sont les sources de financement les plus courantes. Les résultats suggèrent: il existe un potentiel de croissance de l’innovation sociale dans le secteur; il y a moins de liens internes et de regroupement d’initiatives que ne le recommande la théorie de l’innovation; l’accent mis sur la collaboration extérieure rejoint la «troisième mission» des universités, qui existe depuis longtemps, mais les innovateurs sociaux ont des objectifs, des méthodes et des processus distincts pour mener à bien cette mission. Nous concluons avec les orientations pour les recherches futures. Keywords / Mots clés: Universities; Higher education; Social innovation; Community engagement; Service mission; Social change; Canada / Universités; Établissements d’enseignement supérieur; Innovation sociale; Engagement communautaire; Mission de service; Changement social; Canada
Number: 1
Keywords: Canada; Innovation sociale; Libre accès; Rôle des universités; Université

Space configurations for empowering university-community interactions - Dorland, Jens; Clausen, Christian; Jørgensen, Michael Søgaard (Science and Public Policy, 2019)
Some see universities as a possible source of solutions to enable a sustainable transition and overcome societal challenges. Findings from three multisite case studies of Desis Labs, FabLabs, and Science Shops shed light on how universities can help empower communities and solve societal challenges locally. Adopting a sociotechnical and flat relational perspective inspired by science and technology studies (STS), we focus on the material and spatial aspects of how these spaces are configured, thereby ensuring practical relevance for policy makers and practitioners. Applying an analytical generalization methodology, we condense the qualitative data into a typology of three ideal space-types (i.e. affording, mediating, and impact-oriented) that represent specific configurations of actors, researchers, students, communities, spaces, infrastructure, equipment, facilitators, etc. The ideal space-types empower communities in different ways, require different resources to create and operate, and translate differently into specific local contexts.
Analyse centrée sur trois types d’approches collaboratives et issues des résultats et constats du projet TRANSIT (terminé en 2017) : 1. Science Shops, 2. FabLabs, Desis Labs
Keywords: Communauté d'innovation; Laboratoire vivant; Méthodes; Réservé UdeM; Rôle des universités; Université

Co-Creation for Social Innovation in the Ecosystem Context: The Role of Higher Educational Institutions - Kumari, Richa; Kwon, Ki-Seok; Lee, Byeong-Hee; Choi, Kiseok (Sustainability, 2020)
This study examined the role of Higher Educational Institutions (HEIs) in promoting, creating, and sustaining social innovation. Recently, HEIs have extended their contribution beyond the traditional function of teaching and research to perform in socio-economic problem-solving. Considering the increasing trends of higher education involvement in social innovation practices, this study tries to examine the tools such as learning processes and systemic thinking approach that could be helpful to align the function and responsibilities of HEIs towards social innovation. The objective is to develop a theoretical understanding of the "co-creation for social innovation" concept and to understand the functions and activities of HEIs that can contribute to this process. To promote co-creation for social innovation, HEIs should actively encourage collaborative learning tools that focus on open platforms for collective action and systemic change that help them to engage with society and strengthen their collaboration with social actors. Different activities such as mutual learning and knowledge diffusion using a transdisciplinary approach, technology-based learning and collaboration, and relational transformation are key enablers that can promote social innovation.
Place: Basel Publisher: Mdpi WOS:000521955600307 Organsimes de soutien pour bien comprendre le rôle des établissements d’enseignement supérieur Adhésion et pérennisation, puisqu’il est abondamment question de changements systémiques 2e section article (p. 13) : mise en évidence de l’apparition de nouveaux concepts et espaces collaboratifs dans les univeristés. Approches collaboratives : la Table 3 est particulièrement intéressante. Les établissements d’enseignement supérieurs peuvent aussi contribuer à l'innovation sociale. Toutefois, elle doit sortir de l’institutionnel et s’ouvrir dans les modes de formations des étudiantes et étudiants. L’intégration des capacités (et changements de comportenments) liés à l’innovation sociale gagne à être intégré dans la formation.
Keywords: Changement systémique; Co-création; Compétences; Formation; Laboratoires d'innovation; Libre accès; Rôle des universités

Universities as change agents in resource-poor local settings: An empirically grounded typology of engagement models - Petersen, Il-haam; Kruss, Glenda (Technological Forecasting & Social Change, 2021)
University-community engagement is emerging as an important channel for social innovation, requiring universities to act as change agents in their local settings. The role of change agent presents new challenges for universities as it requires going beyond institutional borders to collaborate with non-traditional partners such as informal enterprises, and to stimulate and support innovation that may be seen as relevant to a given local setting only. Universities are thus grappling with finding suitable mechanisms and models for engaging in institutional contexts that are vastly different from traditional formal university- and firm-based settings. Based on empirically rich case study research in a South African township, the paper presents new conceptual insights on how universities can catalyse social change in resource-poor local settings through strategically selecting mechanisms and models of engagement that align with locally-embedded institutions, practices and needs. Four types of engagement models are identified, each relate to different models of entrepreneurship and innovation and thus different modes of learning. The typology distinguishes between dominant, traditional knowledge transfer models, and emergent, socially responsive models that show greater promise for promoting collective agency and effecting systemic social change. The typology can be used to assess current practice and inform future strategies.
Keywords: Afrique; Réservé UdeM; Rôle des universités

Rapid Community Innovation: a Small Urban Liberal Arts Community Response to COVID-19 - Talmage, Craig Allen; Annear, Christopher; Equinozzi, Kate; Flowers, Kathleen; Hammett, Grace; Jackson, Amy; Kingery, Julie Newman; Lewis, Robin; Makker, Kirin; Platt, Audrey; Schneider, Travis; Turino, Caroline (International Journal of Community Well-Being, 2021)
Stories of community resilience and rapid innovation have emerged during the global pandemic caused by COVID-19. As communities, organizations, and individuals have had to shift modalities during the pandemic, they have identified ways to sustain community well-being. Prior to COVID-19, colleges and universities were hailed as anchors of economic and social resilience and well-being for communities of place. In this light, this commentary highlights stories of rapid community innovation occurring at Hobart & William Smith Colleges in the Finger Lakes region of New York. A series of vignettes are presented showcasing lessons and on-going questions regarding rapid pivots, community values, and diversity and inclusion during (and after) the pandemic. Overall, these insights can inform future local collaborative development efforts post-COVID-19 between colleges/universities and their local community.
Keywords: Réservé UdeM; Rôle des universités; États-Unis

Technology-transfer offices and academic open labs as different types of organizational intermediaries in science-society relationships - Mérindol, Valérie; Gallié, Emilie Pauline; Capdevila, Ignasi (Gestion 2000, 2018)
Cet article étudie les caractéristiques des structures de transfert technologique et des laboratoires d’innovation ouverte gérés par les universités et organismes de recherche. Il compare leurs rôles comme intermédiaires des relations science–entreprises en fonction des modes 2 et 3 de production des connaissances proposés par Etzkowitz & al (1997) et Carayannis & al (2009). Basée sur une comparaison de cas multiples en France, nous analysons leur rôle dans le développement des relations science-entreprise. Cet article identifie aussi les modes de coordination entre ces deux types d’intermédiaires. Dans certains cas, ils coordonnent leurs activités de manière ponctuelle alors que, dans d’autres cas, la complémentarité de leurs activités s’organise sur la durée.
Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 1 Publisher: Association de Recherches et Publications en Management
Keywords: Europe; France; Réservé UdeM; Rôle des universités; Technologie; Transfert; Valorisation

Social innovation governance and the role of universities: Cases of quadruple helix partnerships in Italy - Bellandi, Marco; Donati, Letizia; Cataneo, Alessandra (Technological Forecasting and Social Change)
This paper explores the governance of social innovation throughout quadruple helix partnerships between civil society, business, government, and academic actors. Particular attention is given to the participation of universities in such partnerships as an expression of public and community engagement under broad third mission goals. Quadruple helix partnerships may favour the governance of projects aiming at social innovation, but conflicts and drawbacks can hinder the alignment of partners’ contributions. To tackle this issue, we develop a conceptual framework that points out four key phases in such governance processes: i) identification of a common nexus, ii) building of shared strategies, iii) implementation, and iv) learning feedbacks. We apply this framework to three Italian projects under the new EU Urban innovative actions’ program. Different alignment pathways and barriers in the governance process emerge and are discussed. The results show that quadruple helix partnerships for social innovation work smoothly if a solid common nexus between partners is in place. The University is used as a focal actor to understand the mechanisms underpinning each phase and the role it may play in such partnerships.
Keywords: Europe; Gouvernance; Innovation sociale; Partenariat; Quadruple helix approach; Réservé UdeM; Rôle des universités

¿Son las universidades socialmente responsables? - Valle, Maria Belén Arias; Berbegal-Mirabent, Jasmina; Marimon-Viadiu, Frederic (education policy analysis archives, 2021)
The importance of university social responsibility (USR) is given by the commitment assumed by the university towards its stakeholders. This study aims at providing new insights on this topic, by analyzing the level of performance in USR that universities communicate. To this end, a structured procedure in five phases is proposed, analyzing elements of the strategic direction and considering the use of USR indicators which are grouped in the four main areas of impact (organizational, educational, cognitive and social). To do this, a qualitative approach has been followed, supported by the use of text analysis software as well as by frequency and spider diagrams. To illustrate its use and the type of analysis it allows, the procedure is applied to the case of the Catalan higher education system, presenting the results at different levels. The study ends with the discussion of the implications, a list of recommendations and suggestion for future works.
Accès libre
Keywords: Europe; Libre accès; Rôle des universités

Why do universities have little systemic impact with social innovation? An institutional logics perspective - Cinar, Ridvan; Benneworth, Paul (Growth & Change, 2021)
Social innovation has been increasingly regarded as an instrument through which transformative structural change, necessary to address grand societal challenges can be achieved. Social innovations are encouraged by the emergence of innovation systems that support changes not exclusively driven by a techno-economic rationality. In the context of this special issue, there has been both little understanding of social innovation systems within mainstream innovation ecosystem approaches and little analysis of the roles played by universities in social innovation systems. We here focus on the institutional complexity of universities and their field-level dynamics as serving as a potential break on the institutionalisation of social innovation. To deepen our understanding of this, we utilise a literature around institutional logics to foreground characteristics of organisational fields with regard to social innovation. Drawing on empirical data gathered in two public universities located in different countries, we show that in one case the potential of social innovation is undermined by two dominant institutional logics, in the other its permeation across the organisational field is seriously challenged by a more powerful dominant logic. The institutional logic approach is useful to highlighting the barriers to building productive innovation ecosystems incorporating social considerations, and helps to explain the persistent difficulties in reframing ecosystems approaches to reflect wider societal dynamics.
Keywords: Europe; Réservé UdeM; Rôle des universités

Unpacking the role of universities in the emergence, development and impact of social innovations – A systematic review of the literature - Bayuo, Blaise Booponoyeng; Chaminade, Cristina; Göransson, Bo (Technological Forecasting and Social Change, 2020)
Widening income and knowledge inequalities have led to growing expectations for universities to integrate social innovation in their core missions as a response to societal problems. This systematic review of literature provides an overview of the state-of-the-art of knowledge on the role of the university in enabling social innovation through its missions of teaching, research and third mission. It also identifies knowledge gaps in the field. A bibliometric approach wasused to identify and analyze books, journal articles and reports examining factors driving social innovation activities at universities, organizational and insitutional change to accommodate such activities as well as their impact. The review reveals that the literature on university engagement in socially-oriented activities as part of the third mission of the university is conceptually well developed and a growing field of inquiry. It also points to gaps in the knowledge base; relatively few studies address issues related to institutional change and incentive structures that influences the ability of universities to engage in social innovation. Likewise, impact studies on social innovation activities at universities are scarce. Further research that builds an impact measurement framework would support the process of integrating social innovation activities in the three missions of the university.
Num Pages: 1 Place: New York, United Kingdom Publisher: Elsevier Science Ltd.
Keywords: Innovation sociale; Mesure d'impact; Recherche; Réservé UdeM; Rôle des universités; Université

Knowledge transfer for frugal innovation: where do entrepreneurial universities stand? - Fischer, Bruno; Guerrero, Maribel; Guimón, José; Schaeffer, Paola Rücker (Journal of Knowledge Management, 2020)
Frugal innovation has gained prominence based on its potential contribution to sustainable development and the new opportunities that it offers to low-income customers. This paper aims to analyse the strategic knowledge transfer practices implemented by an entrepreneurial university for fostering frugal innovations within an emerging economy. Design/methodology/approach This study adopted a case study methodological approach. The selected case was the University of Campinas (Unicamp), one of the leading universities in Brazil in terms of research quality and technology transfer. The study built upon 14 interviews with key informants and secondary sources of data (official and public documents). Findings The findings highlight the multidimensional dynamics of frugal innovations arising from university–industry relationships. Key dimensions considered include the internal capabilities of universities to foster frugal innovations and connect them to markets, the surrounding innovation ecosystems in which the university is embedded and the overarching institutional framework. Research limitations/implications The analysis of strategic management practices for frugal innovation requires an evolutionary perspective, but the findings lacked sufficient longitudinal information for a formal evaluation. Also, as our empirical analysis is based on an in-depth case study of one university, further validation in other contexts would be necessary. Practical implications This study offers new insights regarding the effectiveness of university-business collaboration partnerships for developing frugal innovations in emerging economies. Policymakers should promote societal programs enhancing the active participation of all agents involved in the entrepreneurial and innovation ecosystem. University managers should understand the challenges and the opportunities behind the adoption of an inclusive and societal orientation. Social implications By adopting frugal innovation practices, universities can enhance their contribution of meeting the United Nations’ Sustainable Development Goals. Originality/value The literature on frugal innovation has emphasized the importance of networking between different types of firms, NGOs and governments, but the role of universities in frugal innovation remains mostly unexplored. This study addresses this gap by exploring how entrepreneurial universities participate in frugal innovations to meet societal challenges.
Publisher: Emerald Publishing Limited
Keywords: Brésil; Innovation frugale; Réservé UdeM; Rôle des universités

Academic Entrepreneurship for Social Innovation in Taiwan: The Cases of the OurCityLove Platform and the Forest App - Chan-Yuan, Wong; Ying-Che, Hsieh; Ching-Yan, Wu; Mei-Chih, Hu (Science, Technology & Society, 2019)
This study attempts to extend the definition of social innovation within the context of academic entrepreneurship. We consider how academic entrepreneurs can undertake commercial activities, and which ones, and how these activities contribute to the contexts of social innovation. We explore two cases that are derived from two premier universities in Taiwan in terms of research and academic entrepreneurship: OurCityLove from National Chiao Tung University (NCTU) and the Forest app from National Tsing Hua University (NTHU). The two cases show how social enterprises achieved the financial ability to expand their businesses and create the desired social values. While the first case, derived from NCTU, focused on providing useful information on social spaces, and services for the elderly, parents traveling with babies and those with disabilities (and also creating job opportunities for the latter), the other from NTHU created an app to influence those addicted to playing with their smartphones. The cases illustrate how the two universities capitalised on their technological competencies and academic programmes to support graduates and researchers in venturing into social entrepreneurship.
Num Pages: 446-464 Place: Thousand Oaks, United States Publisher: SAGE PUBLICATIONS, INC.
Keywords: Asie; Réservé UdeM; Rôle des universités

Innovations in Multistakeholder Partnerships for Sustainable Development: Fostering State–University–Community Nexus - Shaban, Abdul; Narnaware, Prashant B. (People-Centered Social Innovation, 2019)
This chapter shows that there is a possibility of fostering an enabling and innovative multistakeholder partnership for creating sustainable impact and transformative change with local communities. It argues that the collaborative efforts among district administration, educational institutions and civil society groups in supporting innovation and entrepreneurship can play an extremely important role in livelihood security and empowerment of marginalized sections. The chapter outlines the transformation of a marginalized and underdeveloped district of India. It presents a background of the district with a focus on farmers’ distress and discusses the mode of organization of elites and marginalized peoples under welfare and neoliberal regimes. The chapter also outlines the impact that state–university engagement on the communities. The neoliberal regime made the elite-based cooperatives ineffective, as they came under mismanagement and overexploitation by those in power. Neoliberal reform introduced a new vulnerability among Indian farmers, especially in certain states, such as Maharashtra.
Num Pages: 16
Keywords: Asie; Réservé UdeM; Rôle des universités

Universities as Drivers of Social Innovation: Theoretical Overview and Lessons from the "campUS" Research - Fassi, Davide; Landoni, Paolo; Piredda, Francesca; Salvadeo, Pierluigi (Springer, 2020)
Reviews the social role of universities in the urban context Covers themes and models of major interest Explains how to ensure a legacy of grassroots initiatives
Keywords: Mise en valeur; Réservé UdeM; Rôle des universités

A dual-functional social innovation process model for low-cost houses through university-enabled initiative - Belayutham, Sheila; Ibrahim, Che Khairil Izam Che; Zulkifli, Assrul Reedza; Ibrahim, Norhati (Construction Innovation-England, 2019)
The purpose of this study is to develop a dual-functional university-enabled social innovation process model on the subject of low-cost houses that addresses the distinct elements of social obligation and university teaching-learning. Design/methodology/approach This study has predominantly adopted a longitudinal single case study approach, where data have been collected through interviews, survey, participant observation, direct observation and document review. The case study details on the social innovation processes, which was conducted by Universiti Teknologi MARA, Malaysia. Findings This study has demonstrated the social innovation processes toward addressing the issue of insufficient low-cost houses, concurrently benefitting the teaching-learning dimension. Three sub-innovations have been highlighted in the developed social innovation process model, which are collaboration process, teaching-learning and design-construct innovation. Originality/value The development of the social innovation process model for low-cost houses through university-enabled initiative is a novel establishment, particularly for developing nations, as limited studies have been conducted in this regard. The significant insights into how university could play a role in addressing major social issues, along with their core focus (teaching-learning and research development), is a breakthrough for further diffusions of social innovation by universities.
N'AVONS PAS ACCÈS
Keywords: Asie; Enseignement; Innovation sociale; Recherche; Rôle des universités; logement

The role of universities in the development of public sector innovations - Polbitsyn, Sergei N. (The Innovation Journal, 2021)
Studies on public sector innovation often treat this type of innovation as something that emerges within public sector organizations. However, innovation theory argues that external sources of innovation are more fruitful sources of ideas. We claim that universities must be treated as a mandatory element in public sector innovation. This paper is aimed at clarifying the place of public sector innovation in the classification of innovations currently used in the literature. It also seeks to conceptualize an approach for future research on the topic. Our primary goal is to identify the role of different actors in the development of public sector innovation. We analyze the advantages and disadvantages of different forms of university involvement in public sector innovation. The paper consists of two parts. The first defines concepts of innovation in general and public sector innovation viewed as a variation on social innovation. The second is dedicated to an analysis of the experience of Russian universities in enhancing collaboration between actors in the public innovation system.
Num Pages: 1-19 Place: Ottawa, Canada Publisher: The Innovation Journal
Keywords: Asie; Réservé UdeM; Rôle des universités

The potential of ICT-enabled social innovation - Kedmenec, Irena; Detelj, Kristina; Kadoić, Nikola (2019 42nd International Convention on Information and Communication Technology, Electronics and Microelectronics (MIPRO), 2019)
Although social innovation is an old paradigm, social innovation courses appeared in the curricula in the approximately last ten years. By doing so educational institutions acknowledged the existence of new approaches to obstacles that the world is facing. The courses regarding the social innovations give the students valuable knowledge and skills related to solving different social problems, increasing the motivation for being active in the society, and raising awareness about specific topics that need attention. An important role in implementing social innovation have ICT technologies. The role of the ICT is multiple: (1) administrative (members of the certain social initiative collaborate on the project through different ICT tools that enable communication and information organization), (2) disseminative and educational (the topic of the social initiative is disseminated through different tools and social media), and sometimes (3) topical (it the topic of social innovation project is directly connected to specific ICT technology). Based on the roles that the ICT takes upon in the process of social innovation implementation, the authors present ICT solutions that could be included in the realization of a social innovation course for business students at the graduate level.
ISSN: 2623-8764
Keywords: Relations industrielles; Réservé UdeM; Rôle des universités

From Research to Numbers: Role of Universities in Social Innovation - Cunha, Jorge; Ferreira, Carla; Araújo, Madalena; Benneworth, Paul (Innovations in Industrial Engineering, 2022)
Commonly, social innovation is defined as new ideas proposals to the needs of humans. However, there is a lack of a well-definition comprehensive leading the fragmentation of field research. On the other hand, the contribution of universities for social innovation development is still less investigated. In this sense, this study intends to explore interrelations between universities and social innovation in relation to different lines of investigation employed. For this, a content analysis was applied to results obtained by Cunha et al. [1]. Five categories of analysis were defined. Findings revealed that there are a number of studies that applied qualitative research to investigate practical examples of social innovation inside of universities and few empirical studies. A link among keywords social innovation, higher education, and social entrepreneurship was found. Furthermore, the analysis showed that there is not a leader country but a distribution across several countries, where Spain and United Kingdom stand out. Thus, this result suggests that it would be helpful to develop an instrument to measure academics’ engagement with social innovation research and practice. In addition, this research contributes to current knowledge regarding the role of universities in social innovation model, providing new theoretical and practical insights of investigation.
N'AVONS PAS ACCÈS
Keywords: Europe; Rôle des universités

Integrating Social Innovation into the Curriculum of Higher Education Institutions in Latin America: Insights from the Students4Change Project - Unceta, Alfonso; Guerra, Igone; Barandiaran, Xabier (Sustainability, 2021)
In the last two decades, social innovation (SI) and social entrepreneurship (SE) have gained relevance and interest within the framework of academia at international level. Higher education institutions (HEIs) are key players in promoting innovation and social entrepreneurship initiatives that respond to multifaceted challenges. They support strategies on the basis of the strengthening of participation, collaboration, and cooperation with society and its local communities. However, the approach of Latin American universities to SI and SE has been very uneven in the way they have understood them, integrated them into academic programmes, and transferred knowledge to society. On the basis of the experience of the Students4Change project, we sought to understand the role of Latin American HEIs in promoting social innovations by analysing the experiences of 10 participating universities to formalise a pedagogical programme on SI and SE in their institutions. The results suggest that there is still a need to formalise an academic syllabus that is speciﬁcally designed to promote social innovations and to train universities in this endeavour. This paper contributes to the identiﬁcation of the main levers of change, strengths, and challenges that Latin American universities face to institutionalise SI and SE in their contexts.
Keywords: Amérique latine; Libre accès; Rôle des universités

The social impact of universities: assessing the effects of the three university missions on social engagement - Carl, Johannes; Menter, Matthias (Studies in Higher Education, 2021)
Whereas the economic impact of universities is undisputed, the social impact of universities remains vague. The purpose of this paper is to examine whether and how universities influence firms’ social engagement. Based on survey data of more than 7,000 German firms, our results reveal that universities positively affect firms’ social engagement mainly through teaching activities. Hence, our findings give impetus to a reinforcement of the university mission ‘teaching’ as a central lever for social change and increased social awareness as well as to a reorientation of the third university mission toward social needs. This paper thereby contributes to our understanding of the changing missions and values of universities and adds to the literature by exploring the underlying mechanisms of the social impact of universities. We conclude the paper with fruitful future avenues of research.
Keywords: Europe; Réservé UdeM; Rôle des universités

Social Innovation at Technical Universities – State of the Art - Berg, Julia; Leicht-Scholten, Carmen (Proceedings of ISPIM Conferences, 2021)
This paper presents the state of the art in promoting social innovation at five leading technical universities in Europe. We assess how these leading technical universities implement social innovation in their strategies, teaching, and research. The results show that all universities highlight the importance of finding solutions to global challenges and addressing Responsible Research and Innovation (RRI) as a fundamental university strategy for example by promoting social innovation. Moreover, all address the universities’ need to contribute to sustainability and the Sustainable Development Goals. However, social innovation does not play an important role in research and teaching as the results show that social innovation has so far been little addressed in research and teaching. Based on the political framework in the five European countries, we draw up conclusions for technical universities
N'AVONS PAS ACCÈS
Keywords: Europe; Rôle des universités

Contribution of Higher Education Institutions to Social Innovation: Practices in Two Southern European Universities - Monteiro, Sílvia; Isusi-Fagoaga, Rosa; Almeida, Leandro; García-Aracil, Adela (Sustainability, 2021)
The interactions between the higher education sector and society and industry have been attracting increased attention in terms of ways to develop social innovation solutions to societal problems. Despite calls from politicians and the existence of some guidelines, we know little about how higher education could incorporate social innovation activities into its structure and missions. This study examines some practice experiences in two southern European public universities in Portugal and Spain. We show that the third mission of universities, which includes social innovation, is both linked to the first two missions of teaching and research, depending on the university’s historical and social context. The high dependence of higher education institutions on economic returns increases the importance of political action to drive the development of social innovation activities. This conditioning factor seems to be intrinsic to some of the barriers that have been identified, such as lack of legitimization and recognition of social innovation practices at the formal governmental level.
Number: 7 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Europe; Libre accès; Rôle des universités

Digital Innovation during COVID-19: Transforming Challenges to Opportunities - Yu Chen; Roldan, Malu (Communications of the Association for Information Systems, 2021)
The coronavirus disease of 2019 (COVID-19) swiftly changed almost all aspects of our lives and society. In this paper, we depict course adjustments that we made to an undergraduate digital innovation course project, called Innovation Farm (IF), in response to the pandemic. Designed as an in-person course project, IF requires students to create AIpowered Android apps to address important social issues. As stay-at-home orders came into effect in March, 2020, we shifted the course to the online modality refocused its student topics to address social issues that COVID-19 has engendered. Accordingly, we also discuss three challenges that we faced and the strategies we employed to cope with them; namely, framing students' social innovation topics in the COVID-19 context, using virtual studios for online groupwork, and hosting a virtual pitch competition. Surprisingly, these strategies not only addressed the challenges but also created unintended benefits and opportunities. We hope to encourage educators to consider the possibilities in transforming challenges to opportunities during these unprecedented times.
Keywords: Réservé UdeM; Rôle des universités; États-Unis

New Challenges in Universities: Teaching Social Entrepreneurship - Lam-Lam, Suisin; Ahumada-Tello, Eduardo; Plascencia-López, Ismael; Ovalle-Osuna, Oscar Omar; Virginia Barragán-Quintero, Reyna; Evans, Richard David; Soria-Barreto, Karla (2019 IEEE Technology Engineering Management Conference (TEMSCON), 2019)
This study analyses the importance of teaching social entrepreneurship in state universities. A survey was applied to university students to find out if personality traits are related to the characteristics of social entrepreneurship. This was achieved through Alpha Cronbach and Pearson/Spearman correlation analysis. The results show that students have the personality traits to become social entrepreneurs. However, social entrepreneurship courses are not taught in universities of Tijuana city. Therefore, it is strongly suggested to teach social entrepreneurship in universities of the city and the state because students possess social entrepreneurship traits and are interested in the subject.
Keywords: Amérique latine; Réservé UdeM; Rôle des universités

Empowering social innovators through collaborative and experiential learning - Pappas, Ilias O.; Mora, Simone; Jaccheri, Letizia; Mikalef, Patrick (2018 IEEE Global Engineering Education Conference (EDUCON), 2018)
Educating social innovators in higher education is of great importance as many societal challenges exist. This study combines experiential learning with ICT tools to provide students with the needed competences and experiences to solve societal challenges. We employ this approach in an innovative course, named Experts in Teamwork (EiT), which follows the experiential learning cycle. The participants of this study are undergraduate students interested to learn how they can solve societal challenges. Specifically, 26 students with various background and nationalities participated. A collaborative platform was developed that supports teamwork and cooperation, as well as the social innovation process. The findings show that this approach can influence positively learning outcomes and increase students' engagement and motivation with both social innovation and the learning process. Also, students' creativity was increased leading to the development of better solutions. The overall outcomes contribute to theoretical and practical development, to allow educators to take appropriate measures to enhance students' learning experience and foster social innovation through ICT.
ISSN: 2165-9567
Keywords: Réservé UdeM; Rôle des universités

Universities and social innovation for global sustainable development as seen from the south - Arocena, Rodrigo; Sutz, Judith (Technological Forecasting and Social Change, 2021)
Potential contributions of universities to social innovation are explored with special attention to Southern countries. The normative guide is the notion of Sustainable Human Development understood as stressing the agency of least-advantaged sectors. The main challenges stem from decreasing sustainability and increasing inequality. Their impacts are highly dependent on how the tension between economic growth and environmental protection is managed. Improving actual perspectives demands harnessing advanced knowledge to foster inclusive and frugal innovation. For this to occur, universities need to be main actors. The context in which they act is analyzed with reference to the National Systems of Innovation conceptualization. Possible evolutions of universities as agents of social innovation are discussed with the aid of the Multi-Level Perspective. The importance of the Southern experience of innovating in scarcity conditions is highlighted and illustrated with the specific experience of a Latin American university. The cooperation of universities with weak social actors in ways that involve advanced knowledge appears as a key theoretical issue and as a difficult practical problem for the effective engagement of universities in social innovation. The diverse issues that such engagement needs to integrate conform an ambitious research program, of which the paper aims at giving a first glimpse.
Num Pages: 1 Place: New York, United Kingdom Publisher: Elsevier Science Ltd.
Keywords: Amérique latine; Développement Durable-Responsabilité Sociale (DD-RS); Innovation sociale; Réservé UdeM; Rôle des universités

Quelle structuration de la démarche de Développement Durable-Responsabilité Sociale (DD-RS) à l’université ? L’exemple des universités françaises - Petitjean, Jean-Luc; Ory, Jean-Francis; Côme, Thierry (Recherches en Sciences de Gestion, 2021)
L’article est basé sur une enquête portant sur la structuration de la démarche de développement durable et responsabilité sociale (DD-RS) dans les universités françaises. Il s’appuie sur la théorie de la structuration et la Théorie Néo-Institutionnelle pour construire un cadre conceptuel à la structuration de cette mission. Ce dernier est confronté à la pratique des établissements et débouche sur une typologie fondée sur le rôle de l’implication politique, de la culture du pilotage et des isomorphismes. La discussion autour de cette typologie, à partir d’une ACM montrant l’existence de groupes homogènes d’universités quant à leur structuration d’une démarche DD-RS, permet d’affiner le rôle de chacun des facteurs du modèle conceptuel.
Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 0 Publisher: ISEOR
Keywords: Développement Durable-Responsabilité Sociale (DD-RS); Réservé UdeM; Rôle des universités; Théorie Néo-Institutionnelle